THE EFFECT OF INFLATION, DIVIDEND POLICY AND INTEREST RATES ON COMPANY STOCK PRICES - Wijaya, Agung (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This study examines how interest rates, dividend policy, and inflation can affect company value. Using secondary data from Indonesian companies, this study examines inflation, dividend policy, interest rates, and stock price indicators. Purposive sampling was used to select companies for this study. There is no correlation between inflation and stock prices, the study cites. However, interest rates and dividend policies produce limited impact on share value. This study also shows how a company's share price is simultaneously affected by interest rates, dividend policy, and inflation. Based on these findings, it can be concluded that macroeconomic factors such as inflation and interest rates, as well as company financial policies such as dividend policy, play an important role in determining company share prices. It is hoped that the results of this research can become a reference for investors and company management in making investment decisions and financial policies.